2001
DOI: 10.1177/09680519010070011101
|View full text |Cite
|
Sign up to set email alerts
|

Structural variability and originality of the Bordetella endotoxins

Abstract: Structural studies of Bordetella endotoxins (LPSs) have revealed remarkable differences: (i) between their LPSs and those of other bacterial pathogens; (ii) among the LPSs of the seven identified Bordetella species; and (iii) among the LPSs of some Bordetella strains. The lipid As have the "classical" bisphosphorylated diglucosamine backbone but tend to have fewer and species-specific fatty acid components compared to those of other genera. Nevertheless, three strains of B. bronchiseptica have at least three d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 31 publications
(51 reference statements)
2
49
0
1
Order By: Relevance
“…Given the increase in the incidence and the broadening spectrum of human diseases associated with Bordetella hinzii infection (2,13,15,21,22,42,84), it was startling to discover that the data on the bacterial determinants of virulence are limited to lipopolysaccharide (LPS) structure (3,11,85). The lack of research has probably been due, in part, to misidentification of the organism (65) and an early publication by Gerlach et al that indicated that B. hinzii does not possess any of the virulence factors common to the other Bordetella species (25).…”
Section: Discussionmentioning
confidence: 99%
“…Given the increase in the incidence and the broadening spectrum of human diseases associated with Bordetella hinzii infection (2,13,15,21,22,42,84), it was startling to discover that the data on the bacterial determinants of virulence are limited to lipopolysaccharide (LPS) structure (3,11,85). The lack of research has probably been due, in part, to misidentification of the organism (65) and an early publication by Gerlach et al that indicated that B. hinzii does not possess any of the virulence factors common to the other Bordetella species (25).…”
Section: Discussionmentioning
confidence: 99%
“…In mild conditions, the acyloxyacyl ester could be released without splitting the secondary ester linkage between the two fatty acids and characterized by GC-MS. These conditions have been used to determine the structures of many lipid A preparations, such as those of Bordetella (12)(13)(14)(15), Helicobacter (16), and Yersinia (17). We also demonstrated the importance of such a sequential release in the case of Yersinia lipid A structure previously erroneously described as being identical to that of Escherichia coli.…”
mentioning
confidence: 81%
“…These structures were notable for their peculiarly high variability among species and even strains. In B. bronchiseptica, lipid A structural variability has been attributed to relaxed enzyme specificity (6,13,15). The lipids A of two human pathogens, B. pertussis and B.…”
mentioning
confidence: 99%
“…An almost identical core structure to B. pertussis was reported for B. bronchiseptica LPS [15]. The core region of B. parapertussis has a shorter heptasaccharide structure and does not contain the Band A trisaccharide [14]. In contrast to B. pertussis, which produces no O-specific polysaccharide (O-SP), B. bronchiseptica and B. parapertussis synthesize short O-SP containing about 12-18 sugars.…”
Section: Introductionmentioning
confidence: 96%
“…The LPS of all three bordetellae is of low molecular weight, < 10 kDa, rendering their isolated saccharides non-immunogenic. B. pertussis LPS is comprised of a Lipid A domain and a branched dodecasaccharide, composed of unusual sugars with free amino and carboxylic groups [14]. By SDS-PAGE, B. pertussis LPS shows two bands, A and B.…”
Section: Introductionmentioning
confidence: 99%